Aging-Related Molecular Pathways in Chronic Cholestatic Conditions - Pinto, Claudio; Ninfole, Elisabetta; Benedetti, Antonio; Maroni, Luca; Marzioni, Marco (Frontiers in Medicine, 2020)
Aging is commonly defined as the time-dependent functional decline of organs and tissues. Average life expectancy has increased considerably over the past century and is estimated to increase even further, consequently also the interest in understanding the aging processes. Although aging is not a disease, it is the major risk factor for the development of many chronic diseases. Pathologies such as Primary Biliary Cholangitis (PBC) and Primary Sclerosing Cholangitis (PSC) are cholestatic liver diseases characterized by chronic inflammation, biliary damage and ultimately liver fibrosis, targeting specifically cholangiocytes. To date, the influence of aging in these biliary diseases is not fully understood. Currently, liver transplantation is the only solution because of lacking in efficiently therapies. Although liver cells have a high regenerative capacity, they undergo extensive molecular changes in response to aging. Following time-dependent damage induced by aging, the cells initially activate protective compensatory processes that, if hyperstimulated, can lead to the decline of regenerative capacity and the development of pathologies. Recent studies have introduced novel therapeutic tools for cholangiopathies that have showed to have promising potential as novel therapies for PSC and PBC and for the development of new drugs. The recent advancements in understanding of molecular aging have undoubtedly the potential to unveil new pathways for selective drug treatments, but further studies are needed to deepen their knowledge.